1976
DOI: 10.1007/bf02532658
|View full text |Cite
|
Sign up to set email alerts
|

Cholesteryl ester metabolism in tissue culture cells: II. Source of accumulated esterified cholesterol in Fu5AH rat hepatoma cells

Abstract: Previous investigations had demonstrated that Fu5AH rat hepatoma cells accumulated large quantities of esterified cholesterol when grown in hyperlipemic rabbit serum. The present investigation has determined the sources of the cellular esterified cholesterol when the cells were grown in hyperlipemic serum. Cellular esterification of endogenous and exogenous free cholesterol contributed 10% and 30%, respectively. The remaining 60% of the accumulated cellular esterfied cholesterol was derived from exogenous (ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

1976
1976
1983
1983

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(17 citation statements)
references
References 49 publications
2
15
0
Order By: Relevance
“…Cholesterol poor dispersions (FC/P less than one) were prepared with 40 mg of lecithin and less than 20 mg of cholesterol. Albumin (5 mg/ml) was added to the sonicated dispersions and the mixture was centrifuged at 26,000 X g for 30 (12), and the radioactivity in the separated bands was measured by liquid scintillation techniques (11,12). of FC per ml.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cholesterol poor dispersions (FC/P less than one) were prepared with 40 mg of lecithin and less than 20 mg of cholesterol. Albumin (5 mg/ml) was added to the sonicated dispersions and the mixture was centrifuged at 26,000 X g for 30 (12), and the radioactivity in the separated bands was measured by liquid scintillation techniques (11,12). of FC per ml.…”
Section: Methodsmentioning
confidence: 99%
“…EC accumulation in patients with cholesteryl ester storage disease results from a block in the hydrolysis of EC (28), and a similar mechanism has been proposed in atherosclerosis (29). Alternatively, studies on both aorta (25,26) and cells in culture (12,30) have demonstrated that at least a portion of the EC accumulated in these experimental systems is derived from an increased esterification of FC. The present experiments illustrate that cholesterol-rich dispersions promote enhanced cellular FC esterification in Fu5AH cells and that this accelerated esterification leads to EC accumulation comparable to that observed when these cells are grown in hyperlipemic sera (I1, 12).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clair et al, 1977;Rothblat et al, 1976;Mahley et al, 1977;Pearson, 1976). These results are qualitatively similar to those seen in the normal aorta when exposed to hyperlipemic serum in vitro using organ cultures (St. Clair and Harpold, 1975) or in vivo by dietary manipulations (Vesselinovitch et al, 1976;Armstrong and Megan, 1972).…”
mentioning
confidence: 54%
“…ACAT activity was assayed isotopically using [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C palmitoyl CoA as the radioactive substrate. at 260 nm.…”
Section: Enzyme Assaysmentioning
confidence: 99%